Migrazioni al Río de la Plata e critica letteraria in Italia (Altre Modernità, 2009)
In the last twenty-five years the transoceanic migrations have become object of multidisciplinary and interdisciplinary studies (known as ";migrant studies";), by sociologits, anthropologists, psychologists, philosophers, demographers, economists, and - this is of particular interest to us - scholars of literature.In fact, the migration streams have produced on both sides of the Atlantic Ocean a literary corpus regarding all genres of writings, creative and factual. This corpus has attracted the attention of scholars specialized in Italian literature and in Latin-American literatures from countries particularly affected by this phenomenon, like Argentina and Uruguay. This essay will deal with developments and perspectives of this literary production in Italy.
Keywords: Migrations; Rio de la Plata; Italian literature; Latin-American literatures